Natural cycles in South Pacific Gyre strength and the Southern Annular Mode - Nicholas T. Hitt; Daniel J. Sinclair; Helen L. Neil; Stewart J. Fallon; Aimée Komugabe-Dixson; Denise Fernandez; Philip J. Sutton; John C. Hellstrom (Scientific Reports, 2022)
Abstract The South Pacific Gyre (SPG) plays a vital role in regulating Southern Hemisphere climate and ecosystems. The SPG has been intensifying since the twentieth century due to changes in large scale wind forcing. These changes result from variability in the Southern Annular Mode (SAM), causing warming along the eastern SPG which affects local ecosystems. However, our understanding of SPG variability on timescales greater than several decades is poor due to limited observations. Marine sediment cores are traditionally used to determine if recent ocean trends are anomalous, but rarely capture centennial variability in the southwest Pacific and limit our understanding of SPG variability. Here we capture centennial SPG dynamics using a novel high-resolution paleocirculation archive: radiocarbon reservoir ages (R) and local reservoir corrections (∆R) in SPG deep-sea black corals. We find black coral R and ∆R correlates with SAM reconstructions over 0–1000 cal BP and 2000–3000 cal BP. We propose this correlation indicates varying transport of well-ventilated subtropical waters resulting from SPG and SAM interactions. We reconstruct several ‘spin up’ cycles reminiscent of the recent gyre intensification, which has been attributed to anthropogenic causes. This implies gyre strength and SAM show natural co-variability on anthropogenic timescales which should factor into future climate projections.